Precise forging process for high-strength truck cross arm
Through multi-stage forging and special heat treatment of 42CrMo4 alloy steel, combined with nanocomposite coating, the problems of unstable material performance and low production efficiency in the forging process of cross-arm of high-strength trucks in the existing technology are solved, and higher machinery is achieved Performance and lower production costs.
Patent Information
- Application Number
- CN202411516926.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-27
AI Technical Summary
The existing high-strength truck cross-arm forging process is difficult to achieve uniform microstructure and optimized mechanical properties of high-performance alloy steel materials without sacrificing production efficiency, and traditional methods have unstable performance and high cost in terms of heat treatment and surface treatment. question.
42CrMo4 alloy steel is used for chemical composition adjustment, and through multi-stage heating, forming and special heat treatment, including preforging, multi-directional forging, fine forging, cold forging, quenching and multiple tempering, combined with nanocomposite coating, optimize the material's material Microstructure and mechanical properties.
It significantly improves the corrosion resistance and wear resistance of the cross arm, improves production efficiency, reduces costs, and extends the service life of the product, enhancing overall reliability and mechanical properties.
Smart Images

Figure CN119187437A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cross arm processing, in particular to a precision forging process for a high-strength truck cross arm. Background Art
[0002] High-strength truck cross arms are usually made of high-performance alloy steel materials through a precision forging process to meet stringent mechanical load and durability requirements. The precision forging process involves a multi-stage heating, forming and cooling process designed to optimize the structural strength and toughness of the cross arm. This process ensures that the material is evenly distributed throughout the cross arm by precisely controlling the temperature and deformation rate, thereby achieving excellent mechanical properties and dimensional accuracy.
[0003] Existing forging processes generally include two basic types: open die forging and closed die forging. Open die forging is carried out without a closed die cavity and is suitable for large or complex-shaped parts. Closed die forging is carried out in a fully or partially closed die and can produce parts with precise dimensions and smooth surfaces. Both open and closed die forging involve heating the metal to the plastic deformation temperature and then forcing it to fill the die shape through pressure. During the forging process, the metal's grains are refined, improving the material's mechanical properties, especially toughness and fatigue resistance.
[0004] Although the existing forging process has improved the mechanical properties of the material, it still has some shortcomings. When producing key components such as high-strength truck cross arms, the existing traditional forging process is difficult to achieve a uniform microstructure and optimized mechanical properties of high-performance alloy steel materials without sacrificing production efficiency. In addition, traditional processes often require additional heat treatment and surface treatment steps to meet higher performance requirements, which not only increases production costs but also prolongs the manufacturing cycle. Moreover, when processing special alloys, traditional methods often find it difficult to accurately control the heating and cooling rates, resulting in unstable product performance, especially in terms of corrosion resistance and wear resistance. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a high-strength truck cross arm precision forging process, which significantly improves the microstructure and mechanical properties of the material through optimized multi-stage heating, forming and special heat treatment steps. This method effectively improves the corrosion resistance and wear resistance of the cross arm, while improving production efficiency and reducing costs.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A precision forging process for a high-strength truck cross arm, comprising the following steps: Select 42CrMo4 alloy steel and adjust its chemical composition, wherein the vanadium content is 0.1% to 0.2%, the titanium content is 0.02% to 0.05%, and the nickel content is 2% to 3%; The adjusted alloy steel blank is heated to a temperature within a range of 1150°C to 1250°C; Perform multi-stage forging, including pre-forging, multi-directional forging and finish forging; The forged cross arm is cold forged and subjected to controlled cooling treatment; The forged cross arm is subjected to quenching and multiple tempering heat treatments; The cross arm is surface treated to enhance its corrosion and wear resistance; Carry out size and quality inspection to ensure product quality meets standards.
[0007] Preferably, the alloy steel blank is subjected to serial annealing pretreatment before heating, including heating the blank to 690°C to 710°C, maintaining it for 4 to 6 hours, and then naturally cooling it to room temperature in a furnace to improve the machining properties of the blank and the plasticity of subsequent forging.
[0008] Preferably, the heating step further comprises using a zone controlled heating technique while maintaining the temperature range to ensure that the temperature of the blank is evenly distributed over the entire volume to reduce thermal stress.
[0009] Preferably, the multi-stage forging steps include: Pre-forging: It is carried out under a pressure of 4500 tons to 5500 tons to initially form the general shape of the cross arm; Multi-directional forging: applying 5,500 to 6,500 tons of pressure in different directions to optimize the internal microstructure of the material and improve its overall mechanical properties; Precision forging: It is carried out under a pressure of 7,000 to 8,000 tons, using precisely controlled forging dies to ensure the precise dimensions and smooth surface of the final product.
[0010] Preferably, the cold forging and the controlled cooling treatment include being performed on a specially designed cooling bed designed for uniform cooling to avoid uneven shrinkage and internal stress in the product during cooling.
[0011] Preferably, the quenching and multiple tempering heat treatment includes heating the forging to 870°C to 920°C, rapidly cooling to room temperature, and then tempering three times, each tempering temperature is 560°C to 600°C, and the duration is 3 hours to improve the toughness of the material and reduce the hardness.
[0012] Preferably, the surface treatment includes applying a nanocomposite coating with a thickness of 10 μm to 20 μm, which is evenly covered on the surface of the cross arm using a spraying technique to enhance its corrosion resistance and wear resistance.
[0013] Preferably, the quality inspection further includes using laser scanning and a three-dimensional coordinate measuring machine to perform dimensional accuracy testing, and using ultrasonic testing technology to check for internal defects to ensure that the product meets strict industrial standards.
[0014] Preferably, the quenching and multiple tempering heat treatments further include an intermediate cooling step between quenching and tempering, which is performed in air and cooled to room temperature to further optimize the microstructure of the material and improve its subsequent tempering effect to enhance the overall mechanical properties of the cross arm.
[0015] Preferably, the size and quality inspection further includes: Use precision laser scanning equipment to conduct a comprehensive appearance inspection to measure the overall size and appearance features of the cross arm to ensure that the dimensional tolerance is within ±0.5mm; Visually and tactilely inspect the cross arm surface to look for any surface defects such as scratches, dents, and uneven areas; Ultrasonic testing technology is used to conduct a comprehensive internal structural inspection of the cross arm to identify cracks and pores inside it and ensure that the internal quality meets the design specifications; All test results are recorded in the quality assurance system, and products that do not meet specifications are tracked and reworked to ensure that the quality of the final product meets the requirements.
[0016] The present invention provides a precision forging process for a high-strength truck cross arm. It has the following beneficial effects: 1. The precision forging process and special multi-stage heat treatment adopted by the present invention significantly improve the mechanical properties of the forged cross arm. By precisely controlling the heating and cooling rates, the forged cross arm of the present invention exhibits higher tensile strength and improved toughness. This method reduces the internal stress of the material and prevents early failure under heavy load and high fatigue environments, thereby extending the service life of the product and improving the overall reliability.
[0017] 2. The present invention significantly improves the corrosion resistance and wear resistance of the forged cross arm by applying advanced nanocomposite coating. The nanocomposite coating not only provides stronger chemical stability, but also reduces surface wear through its high wear resistance, so that the cross arm can maintain its performance in more harsh environments, such as high salt spray and high humidity conditions.
[0018] 3. The present invention achieves higher production efficiency and lower energy consumption through optimized forging parameters and precise temperature control. Compared with traditional forging methods, the present invention reduces energy waste and raw material usage in the process, and reduces waste generation in the production process, which not only improves the economic benefits of the manufacturing process, but also reduces the negative impact of manufacturing activities on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Please see attached Figure 1 The embodiment of the present invention provides a precision forging process for a high-strength truck cross arm, comprising the following steps: 42CrMo4 alloy steel is selected and its chemical composition is adjusted, wherein the vanadium content is 0.1% to 0.2%, the titanium content is 0.02% to 0.05%, and the nickel content is 2% to 3%. By using 42CrMo4 alloy steel, vanadium, titanium and nickel, the strength and toughness of the alloy can be improved. Vanadium can improve the hardness and wear resistance of steel, titanium helps to refine the grains, and nickel enhances the overall corrosion resistance. By adjusting the chemical composition, the mechanical properties and durability of the cross arm are improved, so that it can be used in more harsh environments, extending the service life of the product; The adjusted alloy steel blank is heated to a temperature within the range of 1150°C to 1250°C. This temperature range is based on the austenitization temperature of 42CrMo4 steel to ensure that the blank is completely austenitized before forging and improve its plasticity. This heating process ensures that the blank has good plasticity during the forging process and reduces material defects such as cracks and holes during the forging process. Multi-stage forging is carried out, including pre-forging, multi-directional forging and fine forging. Multi-stage forging not only improves the shape accuracy of the product, but also improves the internal structure of the material through multi-directional pressure, thereby enhancing the overall performance and reliability of the product; The forged cross arm is cold forged and cooled in a controlled manner. This step effectively reduces the internal stress of the product, prevents deformation and cracks caused by improper cooling rate, and improves the structural integrity and stability of the finished product; The forged cross arm is subjected to quenching and multiple tempering heat treatments. This cyclic heat treatment process is designed to optimize the mechanical properties of the material, obtain hardness through quenching, and adjust toughness through tempering to prevent fracture caused by hardness and brittleness during use; The cross arm is surface treated to enhance its corrosion resistance and wear resistance. The coating is evenly applied through spraying technology to improve the corrosion resistance and wear resistance of the cross arm. The nano coating significantly improves the surface performance of the product, prolongs the service life in harsh environments, and reduces maintenance costs; Carry out dimensional and quality inspections to ensure that product quality meets standards. Comprehensive inspection methods ensure that both product dimensions and internal quality meet design requirements, greatly reducing rework caused by quality issues.
[0022] Please see attached Figure 1 In a preferred embodiment of the present invention, the alloy steel blank is subjected to serial annealing pretreatment before heating, including heating the blank to 690℃~710℃, maintaining for 4~6 hours, and then naturally cooling to room temperature in the furnace to improve the mechanical processing performance of the blank and the plasticity of subsequent forging. After heating to an appropriate temperature, carbides such as vanadium carbide and titanium carbide in the alloy can be dissolved in austenite, making the alloy composition more uniform. In the subsequent heat preservation and slow cooling process, austenite gradually transforms into pearlite and ferrite. This microstructure adjustment helps to improve the plasticity and toughness of the material, while reducing the formation of hard and brittle phases. By optimizing the internal microstructure of the blank, the plasticity of the material is greatly enhanced, so that the blank can withstand greater deformation without cracking in the subsequent forging process. The uniform microstructure and reduced internal stress make the material have better toughness. Serial annealing reduces the possibility of defects in subsequent processing by reducing the internal stress and unevenness of the material, and improves the yield rate and product consistency.
[0023] Please see attached Figure 1 In a preferred embodiment of the present invention, the heating step further includes using a zone-controlled heating technology while maintaining the temperature range to ensure that the temperature of the blank is evenly distributed over the entire volume to reduce the generation of thermal stress. By dividing the blank into multiple heating zones and independently controlling each zone, the distribution of thermal energy can be accurately managed to avoid overheating or underheated areas, achieve uniform heating of the entire blank, reduce internal stress caused by large temperature differences, increase the overall stability and consistency of the forging, and at the same time ensure that the material achieves optimal mechanical properties during subsequent forging and heat treatment processes, avoiding poor performance due to uneven heating.
[0024] Please see attached Figure 1 In a preferred embodiment of the present invention, the multi-stage forging steps include: Pre-forging: It is carried out under a pressure of 4,500 to 5,500 tons to initially form the general shape of the cross arm. Pre-forging quickly shapes the blank into the basic cross arm shape by applying high pressure. At this time, the forging does not pursue precise dimensions. The main purpose is to compress and extend the large blank to a size close to the final shape. Pre-forging reduces the size of the material, which reduces the burden for subsequent detailed forming. At the same time, the microstructure of the material is improved through shaping, laying the foundation for achieving better mechanical properties. Multi-directional forging: 5,500 to 6,500 tons of pressure is applied in different directions to optimize the internal microstructure of the material and improve its overall mechanical properties. The key to multi-directional forging is to further refine the grains, break up and evenly distribute the carbides and other alloy elements in the raw materials through balanced pressure in multiple directions. Multi-directional forging makes the internal microstructure of the cross arm more uniform, enhances its overall mechanical properties, especially improves fatigue resistance and fracture resistance; Precision forging: It is carried out under a pressure of 7,000 to 8,000 tons, using precisely controlled forging dies to ensure the dimensional accuracy and smooth surface of the final product. Precision forging uses precision dies and high pressure to ensure that the blank meets strict manufacturing standards in shape and size. Precision forging not only ensures the accuracy of product size, but also greatly improves surface quality, reduces the need for subsequent machining, and improves production efficiency and the overall quality of the product.
[0025] Please see attached Figure 1 In a preferred embodiment of the present invention, the cold forging and the controlled cooling treatment include being performed on a specially designed cooling bed, which is designed for uniform cooling to avoid uneven shrinkage and internal stress in the product during the cooling process. The cooling bed locally adjusts the flow rate and temperature of the cooling medium to adapt to the areas of different thickness and mass density of the cross arm to achieve a globally balanced cooling effect. Gradual cooling also helps to make the transformation process of residual austenite in the steel to martensite or other phases more stable, reduce the residual untransformed austenite, and improve the mechanical properties and stability of the final product. It not only improves the dimensional accuracy of the product, but also enhances its structural integrity and long-term reliability. The cooling bed is a prior art and will not be described in detail in this article.
[0026] Please see attached Figure 1 In a preferred embodiment of the present invention, the quenching and multiple tempering heat treatment includes heating the forging to 870℃~920℃, rapidly cooling to room temperature, and then tempering three times, each tempering temperature is 560℃~600℃, and the duration is 3 hours to improve the toughness of the material and reduce the hardness. By rapidly cooling the austenitized forging, the carbon and alloy elements in its structure are forced to be supersaturated to form a very hard but brittle martensite structure. Tempering is a process of heat treating the brittle martensite after quenching, aiming to reduce internal stress and transform a part of the martensite into more tough pearlite. Through quenching, the hardness of the forging is significantly improved, which is very important for truck cross arms that require wear resistance and heavy loads. Rapid cooling locks the strength of the material and provides the necessary physical properties for high-performance applications. Multiple tempering not only balances the brittleness introduced by quenching, but also increases the overall toughness of the material by reducing internal stress, making the forging more durable in actual use and reducing the risk of accidental fracture caused by stress concentration.
[0027] Please see attached Figure 1 In a preferred embodiment of the present invention, the surface treatment includes applying a nanocomposite coating with a thickness of 10 μm to 20 μm, which is evenly covered on the surface of the cross arm by spraying technology to enhance its corrosion resistance and wear resistance. Due to its extremely small size, the nanocomposite material can provide very uniform coverage at the molecular level, which helps to form an extremely uniform and dense protective layer. The nanocomposite coating can significantly improve the corrosion resistance of the cross arm, allowing it to be used in more severe environments and extend its service life. The hardness and toughness of the coating make the cross arm have higher wear resistance when frequently used.
[0028] Please see attached Figure 1 In a preferred embodiment of the present invention, the quality inspection further includes using laser scanning and three-coordinate measuring machines to perform dimensional accuracy tests, and cooperating with ultrasonic detection technology to check internal defects to ensure that the product meets strict industrial standards. Laser scanning technology can quickly generate a high-precision surface profile of the workpiece by emitting a laser beam and capturing its reflected signal. Three-coordinate measurement uses a precisely controlled probe to contact specific points on the surface of the workpiece, and evaluates the size and tolerance by measuring the spatial coordinates of these points. Ultrasonic detection technology is based on the propagation characteristics of ultrasonic waves in materials. When ultrasonic waves encounter foreign matter inside the material, they will be reflected and scattered. By analyzing these reflected signals, the location and size of internal defects can be identified. By combining laser scanning, three-coordinate measurement and ultrasonic detection, this quality inspection process can not only ensure the dimensional accuracy of each cross arm, but also deeply identify and evaluate potential internal defects. This comprehensive quality control method greatly improves the reliability and safety of the product and reduces the rework and after-sales service costs caused by quality problems.
[0029] Please see attached Figure 1 In a preferred embodiment of the present invention, the quenching and multiple tempering heat treatment further includes an intermediate cooling step between quenching and tempering, which is carried out in air and cooled to room temperature to further optimize the microstructure of the material and improve its subsequent tempering effect to enhance the overall mechanical properties of the cross arm. After quenching, a large amount of martensite structure is formed inside the material. Although this structure has high hardness, it is also relatively fragile. Through intermediate cooling in air, part of the residual austenite can be transformed into more stable pearlite or other intermediate phases. This slow cooling process helps to reduce internal stress and avoid the generation of quenching cracks. The intermediate cooling step allows the quenched forging to obtain a more balanced microstructure before tempering. This structural optimization not only improves the overall toughness of the material, but also maintains sufficient hardness, so that the cross arm has better performance when subjected to high loads, and reduces the internal stress and potential cracks caused by quenching, significantly improving the reliability of the product.
[0030] Please see attached Figure 1 In a preferred embodiment of the present invention, the size and quality inspection further comprises: Use precision laser scanning equipment to conduct a comprehensive appearance inspection to measure the overall size and appearance features of the cross arm to ensure that the dimensional tolerance is within ±0.5mm. Laser scanning determines the shape and position of the scanned object by measuring the time or phase change of the laser beam reflected back to the sensor, ensuring that the size and shape of each cross arm accurately meets the design specifications, greatly reducing the risk of assembly failure or poor performance due to dimensional problems; Visually and tactilely inspect the cross arm surface to find any surface defects such as scratches, dents, and uneven areas. By inspecting the surface for scratches, dents, or uneven areas, pay special attention to welds or joints, which are often areas where defects are concentrated, so that potential defects can be discovered and resolved in a timely manner; Ultrasonic testing technology is used to conduct a comprehensive internal structural inspection of the cross arm to identify cracks and pores inside it and ensure that the internal quality meets the design specifications. Ultrasonic testing uses the propagation characteristics of sound waves in materials to identify internal structures. When sound waves encounter interfaces or defects inside the material, reflections or scattering will occur. By analyzing these reflected waves, the location and size of the defects can be determined; Through visual and tactile inspection combined with ultrasonic testing, the surface and internal quality of the cross arm is comprehensively evaluated, potential defects are discovered and resolved in a timely manner, and the overall quality and service life of the product are improved; All test results are recorded in the quality assurance system, and products that do not meet the specifications are tracked and reworked to ensure the quality of the final product. The automatic recording and tracking system of quality data not only provides a powerful quality control tool, but also provides data support for product quality management and continuous improvement, ensuring the continuous optimization of the manufacturing process and the steady improvement of product quality.
[0031] In order to better understand the present invention, the above method is described in detail below in conjunction with specific embodiments.
[0032] Example 1: Basic forging process Material selection and pretreatment: Standard 42CrMo4 alloy steel is used without additional chemical composition adjustment; Material annealing treatment: heat the blank to 700℃, keep it for 3 hours, and then cool it naturally.
[0033] Forging and heat treatment: Single stage forging: Full forging is performed under a pressure of 6,000 tons, without multi-directional forging.
[0034] Quenching treatment: heating to 900℃, water quenching cooling; Single tempering: tempering at 580℃ for 2 hours.
[0035] Surface treatment and quality inspection: A simple painting process rather than applying a nanocomposite coating.
[0036] Dimensional testing is performed using traditional dimensional inspection tools (calipers and micrometers), with no laser scanning or ultrasonic testing.
[0037] Example 2: High performance forging process Material selection and pretreatment: Use of 42CrMo4 steel fine-tuned with special alloying elements, including the addition of 0.15% vanadium and 2.5% nickel; Advanced annealing: Heat to 710°C, hold for 6 hours, and cool slowly using controlled cooling technology.
[0038] Forging and heat treatment: Multi-stage forging: including pre-forging, multi-directional forging and finishing forging, using different pressure increases; Quenching and multiple tempering: After quenching, intermediate cooling in air is carried out, followed by three temperings, each at 600°C for 3 hours.
[0039] Surface treatment and quality inspection: A nanocomposite coating with a thickness of 20 μm was applied; Comprehensive dimensional and visual inspections are performed using laser scanning and CMM, combined with ultrasonic testing of internal structures.
[0040] Example 3: Customized forging process Material selection and pretreatment: Using customized high-strength steel, with 0.2% vanadium, 0.05% titanium and 3% nickel added; The material undergoes a specially designed annealing process, including a two-stage annealing: first heated to 720°C for 4 hours, cooled to 650°C and then held for another 4 hours, and finally air-cooled to room temperature.
[0041] Forging and heat treatment: Adopt innovative forging technologies, such as simultaneous multi-directional pressure forging, to ensure the material's performance consistency in all directions; An innovative quenching process, including rapid cooling and gradual temperature rise tempering cycles, is performed four times to optimize mechanical properties.
[0042] Surface treatment and quality inspection: The newly developed high wear-resistant nanotechnology coating is applied, with the thickness controlled at 15μm; High-end digital inspection systems, including laser microscopes and fully automatic ultrasonic inspection devices, are used to conduct comprehensive quality analysis and records.
[0043] Comparative experiment 1: Mechanical properties test Experimental purpose: To evaluate the effect of the forging process of the present invention and the traditional forging process in improving the mechanical properties of forgings.
[0044] Experimental design: Sample preparation: Control group A: The cross arm was produced using conventional forging and heat treatment processes.
[0045] Control group B: using the conventional forging process but adopting the heat treatment process of the present invention.
[0046] Experimental group: using the full set of precision forging and special heat treatment processes of the present invention.
[0047] Test items: Tensile test: Determine the maximum tensile strength of the sample.
[0048] Compression test: Determination of the deformation and strength of a sample under compressive load.
[0049] Impact test: Determine the toughness of samples under rapid impact load.
[0050] Experimental steps: Sample marking and recording: Each sample is numbered and recorded with its specific manufacturing process details.
[0051] Test machine preparation: Calibrate tensile, compression and impact testing machines to ensure accurate test data.
[0052] To perform a tensile test: Secure the sample in the grips of the tensile testing machine; Gradually increase the tensile force until the sample breaks; The maximum force and elongation at break were recorded.
[0053] To perform a compression test: Place the sample in a compression testing machine; Gradually increase the pressure until the preset maximum pressure is reached or the sample undergoes plastic deformation; The maximum pressure and the corresponding deformation are recorded.
[0054] To perform an impact test: Mount the sample on the impact testing machine; Release the hammer and allow it to impact the sample; Record the absorbed energy and observe the fracture of the sample The comparative experimental data are shown in Table 1: Table 1 Mechanical properties comparison test results type Maximum tensile strength (MPa) Elongation(%) Maximum compression load (kN) Compression deformation(mm) Impact Energy(Joules) Control group A 620 12 1100 0.8 15 Control group A 615 13 1120 0.9 16 Control group B 650 15 1150 0.7 20 Control group B 655 14 1145 0.75 21 Experimental Group 680 18 1200 0.5 25 Experimental Group 675 17 1190 0.55 24 From the data in Table 1, we can get: The data show that the experimental group is superior to the control groups A and B in terms of tensile strength, elongation, maximum compression load, compression deformation and impact energy, indicating that the forging process of the present invention has a significant effect in improving mechanical properties.
[0055] Comparative experiment 2: Corrosion resistance and wear resistance test Experimental purpose: To evaluate the effects of the process of the present invention and the traditional process in improving the corrosion resistance and wear resistance of forgings.
[0056] Experimental design: Sample preparation: Control Group A: Crossarm using conventional forging and surface treatment techniques.
[0057] Control group B: using the conventional forging process, but using the nanocomposite material of the present invention as the coating.
[0058] Experimental group: using the forging process and nanocomposite coating of the present invention.
[0059] Experimental steps: Sample preparation and labeling: Each sample is numbered and documented, detailing its manufacture and processing.
[0060] Corrosion resistance test: All samples were placed in a salt spray test chamber and exposed to 5% salt water mist for 500 hours; Regularly check and record the corrosion condition of the sample surface, mainly observing the formation and spread of rust.
[0061] Wear resistance test: Use a standard wear tester to set a certain wear load and time to perform cyclic wear; The weight difference of the sample before and after wear was recorded, and the microscopic image analysis of the worn surface was performed.
[0062] The comparative experimental data are shown in Table 2: Table 2 Comparative test results of corrosion resistance and wear resistance type Salt spray test time (h) Initial weight (g) Weight after wear (g) Weight difference (mg) Corrosion level Remark Control group A 500 1200 1193 7 medium Significant rust Control group A 500 1205 1196 9 medium Significant rust Control group B 500 1202 1199 3 slight Slight rust Control group B 500 1200 1198 2 slight Slight rust Experimental Group 500 1203 1202 1 small No obvious rust Experimental Group 500 1204 1203 1 small No obvious rust From the data in Table 2, we can get: The control group A showed a higher weight loss and a moderate corrosion grade after the salt spray test, indicating that its corrosion resistance was poor, the control group B showed improved corrosion resistance and a lower wear rate, and the present invention showed the best corrosion resistance and wear resistance, with almost no obvious rust and minimal weight difference, verifying the effectiveness of the nanocomposite coating.
[0063] Comparative experiment 3: fatigue durability test Experimental purpose: To verify the ability of the process of the present invention and the traditional process in improving the fatigue durability of forgings.
[0064] Experimental design: Sample preparation: Control group A: Cross arm using conventional forging and heat treatment process.
[0065] Control group B: using the conventional forging process but adopting the heat treatment process of the present invention.
[0066] Experimental group: using the full set of precision forging and special heat treatment processes of the present invention.
[0067] Experimental steps: Sample marking and recording: Each sample is numbered and documented, detailing its specific manufacturing process.
[0068] Fatigue testing machine preparation: Calibrate the fatigue testing machine to ensure the accuracy of the test data.
[0069] Perform fatigue testing: The samples were mounted on a fatigue testing machine.
[0070] Set the frequency and amplitude of cyclic load to simulate the working conditions in actual use; Perform cyclic load test until the sample suffers fatigue failure; The fatigue life, i.e. the number of cycles to failure, was recorded for each sample.
[0071] The comparative experimental data are shown in Table 3: Table 3 Fatigue durability comparison test results type Cyclic load (kN) Cycle frequency (Hz) Fatigue life (10,000 cycles) Remark Control group A 50 5 0.50 Early destruction Control group A 50 5 0.52 Early destruction Control group B 50 5 0.75 Advanced microcracks Control group B 50 5 0.78 Advanced microcracks Experimental Group 50 5 1.20 No obvious damage Experimental Group 50 5 1.25 No obvious damage From the data in Table 3, we can get: The control group A exhibited a shorter fatigue life under the same test conditions, indicating that its durability under long-term load was poor. The control group B showed a slightly better fatigue life, but the problem of microcracks still existed. The present invention showed the best fatigue life, and the number of cycles was significantly more than the other two groups, which proved the effectiveness of the present invention in improving fatigue durability.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A precision forging process for a high-strength truck cross arm, characterized in that: The following steps are involved: Select 42CrMo4 alloy steel and adjust its chemical composition, wherein the vanadium content is 0.1% to 0.2%, the titanium content is 0.02% to 0.05%, and the nickel content is 2% to 3%; The adjusted alloy steel blank is heated to a temperature within a range of 1150°C to 1250°C; Perform multi-stage forging, including pre-forging, multi-directional forging and finish forging; The forged cross arm is cold forged and subjected to controlled cooling treatment; The forged cross arm is subjected to quenching and multiple tempering heat treatments; The cross arm is surface treated to enhance its corrosion and wear resistance; Carry out size and quality inspection to ensure product quality meets standards.
2. The precision forging process of a high-strength truck cross arm according to claim 1 is characterized in that: The alloy steel blank is subjected to serial annealing pretreatment before heating, including heating the blank to 690°C to 710°C, maintaining it for 4 to 6 hours, and then naturally cooling it to room temperature in a furnace to improve the machining performance of the blank and the plasticity of subsequent forging.
3. The precision forging process of a high-strength truck cross arm according to claim 1 is characterized in that: The heating step further includes using a zoned controlled heating technique while maintaining the temperature range to ensure that the temperature of the blank is evenly distributed over the entire volume to reduce thermal stress.
4. The precision forging process of a high-strength truck cross arm according to claim 1 is characterized in that: The multi-stage forging steps include: Pre-forging: It is carried out under a pressure of 4500 tons to 5500 tons to initially form the general shape of the cross arm; Multi-directional forging: applying 5,500 to 6,500 tons of pressure in different directions to optimize the internal microstructure of the material and improve its overall mechanical properties; Precision forging: It is carried out under a pressure of 7,000 to 8,000 tons, using precisely controlled forging dies to ensure the precise dimensions and smooth surface of the final product.
5. The precision forging process of a high-strength truck cross arm according to claim 1, characterized in that: The cold forging and the controlled cooling treatment include being performed on a specially designed cooling bed, which is designed to uniformly reduce the temperature to avoid uneven shrinkage and internal stress in the product during the cooling process.
6. The precision forging process of a high-strength truck cross arm according to claim 1, characterized in that: The quenching and multiple tempering heat treatment includes heating the forging to 870°C to 920°C, rapidly cooling to room temperature, and then tempering three times, each tempering temperature is 560°C to 600°C, and the duration is 3 hours to improve the toughness of the material and reduce the hardness.
7. The precision forging process for a high-strength truck cross arm according to claim 1, characterized in that: The surface treatment includes applying a nano composite material coating with a thickness of 10 μm to 20 μm, and the coating is evenly covered on the surface of the cross arm by spraying technology to enhance its corrosion resistance and wear resistance.
8. The precision forging process for a high-strength truck cross arm according to claim 1, characterized in that: The quality inspection further includes dimensional accuracy testing using laser scanning and three-dimensional coordinate measuring machines, and checking for internal defects with ultrasonic testing technology to ensure that the product meets strict industrial standards.
9. The precision forging process for a high-strength truck cross arm according to claim 1, characterized in that: The quenching and multiple tempering heat treatment further includes an intermediate cooling step between quenching and tempering, which is performed in air and cooled to room temperature to further optimize the microstructure of the material and improve its subsequent tempering effect to enhance the overall mechanical properties of the cross arm.
10. The precision forging process of a high-strength truck cross arm according to claim 1, characterized in that: The size and quality inspection further includes: Use precision laser scanning equipment to conduct a comprehensive appearance inspection to measure the overall size and appearance features of the cross arm to ensure that the dimensional tolerance is within ±0.5mm; Visually and tactilely inspect the cross arm surface to look for any surface defects such as scratches, dents, and uneven areas; Ultrasonic testing technology is used to conduct a comprehensive internal structural inspection of the cross arm to identify cracks and pores inside it and ensure that the internal quality meets the design specifications; All test results are recorded in the quality assurance system, and products that do not meet specifications are tracked and reworked to ensure that the quality of the final product meets the requirements.
Citation Information
Cited By
High-precision lithium battery slitting cutter machining system
CN120243822A
